Protease with fibrinolytic and collagenolytic activity produced by Aspergillus ochraceus URM604 (Research, Society and Development, 2022)
Proteases play a fundamental role in the economy, being present in several industrial sectors. Among the fungi known to produce proteases, the genus Aspergillus stands out. Thus, the objective of this work was to produce proteases from solid state fermentation of Aspergillus ochraceus, purify, characterize and evaluate their potential in the production of collagenolytic and fibrinolytic enzymes. For this, the type and quantity of the substrate and the humidity of the fermentations were evaluated. Subsequently, purification was performed by DEA-Sephadex and Superdex-G75 chromatography in an FPLC system. As well as partial characterization evaluating the optimal pH and temperature of the protease action. It was observed that the best enzyme activity in fermentations with wheat bran as substrate (3g) and 60% moisture, showing protease, collagenolytic and fibrinolytic activity. Greater activity was also observed at pH8 and 50°C. Thus, it was concluded that A. ochraceus has great potential for biotechnological application, highlighting the importance of future evaluations.